Levine, Alison J. Murray. Vivre Ici: Space, Place, and Experience in Contemporary French Documentary. Liverpool UP, 2018. - Tessa Ashlin Nunn (Studies in 20th & 21st Century Literature, 2019)
Review of Levine, Alison J. Murray. Vivre Ici: Space, Place, and Experience in Contemporary French Documentary. Liverpool University Press, 2018.
Keywords: Documentary; Embodied Spectatorship; Contemporary France